Study on gravity calculation method of integration about an upper extremity exoskeleton and loads. (October 2019) - Feng, Lin; Song, Qiuzhi; Qi, Zhuo; Wang, Xin
Abstract: The gravity center of integration about the upper extremity exoskeleton and loads has a great impact on the balance control of the systemic exoskeleton system. In this paper, a new method is presented to calculate the gravity of the integration. First, build a model of the upper extremity exoskeleton by standard D-H method, analyze the model by kinematics and then obtain the function of the gravity center by analyzing the relationship between the structure parameters, joint angles and gravity center of the integration. Second, simulate each curve of the gravity center with lifting the load of 0, 10KG and 20KG under a specific trajectory determined by cycloid interpolation method. This paper lays a foundation to study on the balance control of the systemic exoskeleton system.